PATOGENISITAS JAMUR ENTOMOPATOGEN Beauveria bassiana Balsamo (DEUTEROMYCETES: MONILIALES) PADA LARVA Spodoptera litura Fabricius (LEPIDOPTERA: NOCTUIDAE) - Agung Setyo Budi; Aminudin Afandhi; Retno Dyah Puspitarini (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
Armyworm (Spodoptera litura F.) is considered one of serious pests attackingleaves due to its parasitic characteristic on most hosts such as soybeans, peanuts,cabbage, sweet potatoes, potatoes. Beauveria bassiana (Balsamo) Vuillemin isprospective to be developed as biological controlling agent which can damage andeven cause death to larvae in orders of Lepidoptera, Coleoptera, Hemiptera andOrthoptera. The objective of this research was to find out pathogenicity of B.bassiana at density of 105, 106, 107, 108,and 109 conidia/ml on larvae S. litura andits influence on the success of larvae S. litura in becoming pupa. The research wascarried out in Mycologi and Growth Chamber laboratory, Pest and Plant DeseaseDepartment, Agriculture Faculty, Brawijaya University, from Desember 2011 toMay 2012. This research applied completely randomised design with threereplicates and density of B. bassiana at: 0 (as control), 105, 106, 107, 108, 109conidia/ml. Each density held 20 larvae. Dipping method was employed in thispathogenicity test, where larvae S. litura was dipped into density suspension of B.bassiana conidia for about 5 seconds and dried. The results of the researchshowed that the highest density rate causing the death of larvae S. litura was at1,47 x 109 conidia/ml with the death of 51,37 %. While the lowest density ratecausing larvae S. litura to become pupa was at 1,47 x 109 conidia/ml with thesuccess rate of larvae S. litura in becoming pupa of 48,63 %. The fastest densityB. bassiana rate causing Median Lethal Time (LT50) on larvae S. litura at 1,47 x109 conidia/ml in 298,97 hours.Key words: Spodoptera litura, Beauveria bassiana, Pathogenicity.